2013
DOI: 10.1021/nn303973r
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Dynamics in Suspended Monolayer and Few-Layer MoS2 2D Crystals

Abstract: Femtosecond transient absorption spectroscopy and microscopy were employed to study exciton dynamics in suspended and Si 3 N 4 substrate-supported monolayer and few-layer MoS 2 2D crystals. Exciton dynamics for the monolayer and few-layer structures were found to be remarkably different from those of thick crystals when probed at energies near that of the lowest energy direct exciton (A exciton). The intraband relaxation rate was enhanced by more than 40 fold in the monolayer in comparison to that observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

110
806
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 744 publications
(919 citation statements)
references
References 41 publications
110
806
2
1
Order By: Relevance
“…While they hypothesized that at such short time scale the initially generated excitons may not be thermalized, recent measurements with femtosecond resolution showed that thermalization for ∼3 eV excitation occurs in less than 1 ps. 18 For this reason, the signal observed in ref 21 can be attributed to the intrinsic radiative decay time of the A exciton at 4 K. This is confirmed by the work from Lagarde et al, 22 who recently measured the timeresolved PL of monolayer MoS 2 excited resonantly at the A exciton and observed a PL decay time of 4.5 ps, in excellent agreement with our computed value.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…While they hypothesized that at such short time scale the initially generated excitons may not be thermalized, recent measurements with femtosecond resolution showed that thermalization for ∼3 eV excitation occurs in less than 1 ps. 18 For this reason, the signal observed in ref 21 can be attributed to the intrinsic radiative decay time of the A exciton at 4 K. This is confirmed by the work from Lagarde et al, 22 who recently measured the timeresolved PL of monolayer MoS 2 excited resonantly at the A exciton and observed a PL decay time of 4.5 ps, in excellent agreement with our computed value.…”
supporting
confidence: 91%
“…They tentatively attribute the 2 ps time to exciton trapping at defects, the 75 ps to hot carrier thermalization, and the 0.85 ns to radiative A exciton recombination. 18 We obtain an effective radiative lifetime of 0.82 ns at room temperature, which is in excellent agreement with the 0.85 ns decay signal observed experimentally. This result indicates that the room-temperature radiative lifetime is of order 1 ns at room temperature and corresponds to the longer PL decay component observed in time-resolved PL experiments.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The behaviors of excitons and trions have strong influence on optical phenomena including absorption and light emission. Reported by many groups, spin‐orbit coupling effect induces the valence band edge of monolayer MoS 2 to split, and the maximum of split locates at the K point of the Brillouin zone, while the minimum of conduction band also locates at K point 38, 39, 40. At the K point of Brillouin zone, the split transition band corresponds to two strongly bound A exciton and B exciton, of which the split band transition energy in monolayer MoS 2 is approximately 1.92eV and 2.08eV, and induces two separated absorption peaks in red to near infrared region.…”
Section: Plasmonic Properties Of 2d Nanomaterialsmentioning
confidence: 99%